Wagner Group: An instrument of Russian foreign policy? | Grupo Wagner: Um instrumento de Política Externa da Rússia? - Conceição da Silva Ferreira, Carla; Kostiuk, Oleksandra; Preisigke Luxinger Rodrigues, Yegho (Political Observer | Revista Portuguesa de Ciência Política (Portuguese Journal of Political Science), 2024)
In an international context where states seek to diversify their means of external projection, consistent with their traditionalism, Russia maintains a traditional vision of power. In this context, the Wagner Group has emerged as a new instrument that can be used in the pursuit of Russian interests and objectives abroad. Through a comparative case study that draws on Western and Russian academic and journalistic sources, as well as Russian strategic and legal documents, the research aims to understand the role of the Wagner Group in Russian foreign policy. To this end, we begin by investigating the concept of a private military company, then we look into the Group’s origin, history of operations and modus operandi. In addition, we identify other ‘Western’ private military companies and compare their activities and the level of scrutiny they receive in relation to the Russian group. We conclude our research by identifying attempts by international law to respond to the emergence of Wagner and other private military groups.